Home care service for children/adolescents with special health care needs: family perception - Paloma Mayara Vieira de Macena Lima; Leiliane Teixeira Bento Fernandes; Mariana Matias Santos; Maria Eduarda Pires Lima Cavalcante; Eliane Tatsch Neves; Beatriz Rosana Gonçalves de Oliveira Toso; Neusa Collet; Elenice Maria Cecchetti Vaz (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To apprehend the family's perception of the care provided by home care services to children and adolescents with special health needs. Method: Qualitative, exploratory-descriptive study, carried out with 15 family members of children and adolescents with special health needs served by Home Care Services in seven municipalities in Paraíba, in 2021, selected from nine municipalities identified by previous studies. Data were collected using semi-structured interviews carried out remotely through telephone calls. The empirical material was subjected to Inductive Thematic Analysis and interpreted in light of the concept of health vulnerability. Results: The Home Care Services facilitate minimize the health vulnerabilities of these children and adolescents and their families as they facilitate access to the actions and services of the Health Care Network, provide humanized care focused on promoting health and strengthening bonds, as well as how, they facilitate family decision-making at home regarding users' health needs. Final considerations: The actions of these services permeate family daily life, enabling the expansion of care practices for family members/caregivers considering their limitations and improving the coordination of Health Care Networks to guarantee comprehensive care.